Assaying nonspecific phospholipase C activity - Pejchar, Přemysl; Scherer, Günther F E; Martinec, Jan (Methods in molecular biology (Clifton, N.J.), 2013)
Plant nonspecific phospholipase C (NPC) is a recently described enzyme which plays a role in membrane rearrangement during phosphate starvation. It is also involved in responses of plants to brassinolide, abscisic acid (ABA), elicitors, and salt. The NPC activity is decreased in cells treated with aluminum. In the case of salt stress, the molecular mechanism of NPC action is based on accumulation of diacylglycerol (DAG) by hydrolysis of phospholipids and conversion of DAG, the product of NPC activity, to phosphatidic acid (PA) that participates in ABA signaling pathways. Here we describe a step-by-step protocol, which can be used to determine in situ or in vitro NPC activity. Determination is based on quantification of fluorescently labeled DAG as a product of cleavage of the fluorescently labeled substrate lipid, phosphatidylcholine. High-performance thin-layer chromatography is used for separation of fluorescent DAG. The spot is visualized with a laser scanner and the relative amounts of fluorescent DAG are quantified using imaging software.
Keywords: Substrate Specificity; fluorescenční barviva; Diglycerides; rostliny; enzymatické testy; Reference Standards; Type C Phospholipases; fosfolipasy typu C; referenční standardy; chromatografie na tenké vrstvě; Enzyme Assays; substrátová specifita; diglyceridy; Plants; Chromatography, Thin Layer; Fluorescent Dyes